2018
DOI: 10.5539/jas.v10n10p308
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutrient Uptake of Common Bean Cultivars as Affected by Plant Population and Growing Season

Abstract: Brazil’s production of common bean is insufficient to supply the domestic market. Factors such as plant density, cultivar, growing season, and nutrient uptake affect bean yield, suggesting the need for more studies to optimize bean production. The objective of this work was to evaluate the effect of plant density on seed yield components and nutrient uptake of two common bean cultivars grown in two different seasons. Field experiments were carried out at the IAPAR experimental site in Santa Tereza do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Common bean studies have shown a linear decrease in pods per plant with increasing density [13]. In this study, the response of the cultivars to planting density in terms of pods per plant and hundred seed weight (HSW) varied between growing seasons according to cultivar and available soil moisture (Figure 3A,B).…”
Section: Pods Per Plant and Hundred Seed Weightmentioning
confidence: 68%
See 1 more Smart Citation
“…Common bean studies have shown a linear decrease in pods per plant with increasing density [13]. In this study, the response of the cultivars to planting density in terms of pods per plant and hundred seed weight (HSW) varied between growing seasons according to cultivar and available soil moisture (Figure 3A,B).…”
Section: Pods Per Plant and Hundred Seed Weightmentioning
confidence: 68%
“…Planting at high densities can be a strategy for obtaining optimum yield [9,10], although some studies have also shown its limiting effects on aspects of plant growth and development [11][12][13]. In this regard, it is essential to understand the effects of plant density on yield and its components by analyzing influencing factors and identifying major yield-density response curves [14].…”
Section: Introductionmentioning
confidence: 99%